2019
DOI: 10.1111/ilr.12141
|View full text |Cite
|
Sign up to set email alerts
|

To work or not to work: Variables affecting non‐financial employment commitment over time

Abstract: The most common indicator of non‐financial employment commitment (NFEC) is the “lottery question” – whether a person would continue working if they won a lottery. This cross‐sectional research seeks to identify the demographic variables and the “meaning of work” dimensions that could predict individual NFEC, presenting the main international findings over time, with particular reference to data collected in Israel in 1981, 1994 and 2006. The authors' findings point to a marked decrease in NFEC in the new mille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…As a result, the work centrality among this population will decrease (Misumi & Yamori, 1991;Dosman et al, 2006;Froidevaux & Hirschi, 2015). These findings coincide with a lowered willingness to work in the absence of an economic constraint among older people (Mannheim & Rein, 1981;Sharabi & Harpaz, 2019). Furthermore, people who are actual retirees grants lower importance to work, in comparison to employed groups, while granting higher importance to family and community domains (Harpaz, 1990;MOW, 1987).…”
Section: Retirement and Work Centralitymentioning
confidence: 97%
See 3 more Smart Citations
“…As a result, the work centrality among this population will decrease (Misumi & Yamori, 1991;Dosman et al, 2006;Froidevaux & Hirschi, 2015). These findings coincide with a lowered willingness to work in the absence of an economic constraint among older people (Mannheim & Rein, 1981;Sharabi & Harpaz, 2019). Furthermore, people who are actual retirees grants lower importance to work, in comparison to employed groups, while granting higher importance to family and community domains (Harpaz, 1990;MOW, 1987).…”
Section: Retirement and Work Centralitymentioning
confidence: 97%
“…Varied studies found that employee's high work centrality, related to high job performance, work involvement, motivation, organization commitment etc. (Rosso et al, 2010;Sharabi & Harpaz, 2019;Diefendorff et al, 2002). Therefore, employee's work centrality has an impact on organizational performance and success.…”
Section: The Rationale Of the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…USA, South Korea) than in less developed countries (e.g. Brazil, Poland, Russia) (Sharabi and Harpaz, 2019). Note, however, that Snir (2014) used a different measurement (e.g.…”
Section: Review Of the Literaturementioning
confidence: 99%